Performance of lightweight cement-based and alkali-activated mortars exposed to high-temperature. (30th September 2019) - Giosuè, Chiara; Mobili, Alessandra; Di Perna, Costanzo; Tittarelli, Francesca
Highlights: CEM and AAM mortars behave differently at high temperature. In CEM mortars, substitution of cement by 40% MK enhances the resistance up to 1000 °C. In AAM, substitution of MK by 50% FA enhances the resistance up to 1000 °C. The high resistance is due to new crystalline phases formed at high temperatures. Abstract: The behavior of lightweight cement-based and alkali-activated mortars after exposure to temperatures of 500, 750, and 1000 °C was compared. In cement-based mortars, cement was partially replaced (40 vol%) by several refractory fillers (coal fly-ash, biomass fly-ash, cocciopesto, metakaolin). In alkali-activated mortars, metakaolin was partially substituted (0, 25, 50 wt%) by coal fly-ash. The substitution of cement by 40% metakaolin and the substitution of metakaolin by 50% fly ash enhances the resistance to high temperatures of cement-based and alkali-activated mortars, respectively. After exposure to 1000 °C, the high residual compressive strength of cement-based mortars with metakaolin is due to the formation of new crystalline species, whereas in alkali-activated mortars is due to their high densification.